2022
DOI: 10.1038/s41467-022-29323-3
|View full text |Cite
|
Sign up to set email alerts
|

Silver-catalyzed site-selective C(sp3)−H benzylation of ethers with N-triftosylhydrazones

Abstract: The insertion of carbenes into the α-C–H bonds of ethers represents one of the most powerful approaches to access polysubstituted α-branched ethers. However, intermolecular carbene insertions remain challenging, since current approaches are generally limited to the use of toxic and potentially explosive α-diazocarbonyl compounds. We now report a silver-catalyzed α-C–H benzylation of ethers using bench-stable N-triftosylhydrazones as safe and convenient carbene precursors. This approach is well suited for both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 66 publications
0
29
0
1
Order By: Relevance
“…Notably, our method tolerates well the presence of halogen groups (7−12), which are useful synthetic handles for further manipulation with classical transition-metal-promoted cross-coupling reactions. 15 Next, we found that a diverse range of heteroaryl aldehydes, such as picolinaldehyde (21), nicotinaldehydes derivates (22)(23)(24), indazole (25) and indole (26) were compatible with our reaction protocol. Also, several aliphatic aldehyde-derived sulfonyl hydrazones were subjected to our reaction conditions and afforded the targeted C−H alkylated products, albeit with diminished yields (34−45%, 27−29).…”
Section: Table 1 Optimization Of Reaction Conditions Of Both Photocat...mentioning
confidence: 80%
See 1 more Smart Citation
“…Notably, our method tolerates well the presence of halogen groups (7−12), which are useful synthetic handles for further manipulation with classical transition-metal-promoted cross-coupling reactions. 15 Next, we found that a diverse range of heteroaryl aldehydes, such as picolinaldehyde (21), nicotinaldehydes derivates (22)(23)(24), indazole (25) and indole (26) were compatible with our reaction protocol. Also, several aliphatic aldehyde-derived sulfonyl hydrazones were subjected to our reaction conditions and afforded the targeted C−H alkylated products, albeit with diminished yields (34−45%, 27−29).…”
Section: Table 1 Optimization Of Reaction Conditions Of Both Photocat...mentioning
confidence: 80%
“…[17][18][19][20] To realize this synthetic goal, we were drawn to Nsulfonyl hydrazones, which are stable, crystalline compounds and are readily synthesized from the corresponding aldehydes (Figure 1a). [21][22][23][24] Notably, these N-sulfonyl hydrazones can be exploited as a suitable electrophilic site for both polar and radical addition to yield, upon dinitrogen and sulfinate extrusion, the targeted C(sp 3 )-C(sp 3 ) bonds. [25][26][27][28][29][30][31][32] To realize a metalfree protocol, we anticipated that a photocatalytic Hydrogen Atom Transfer (HAT) strategy would be appealing to activate aliphatic C-H bonds, [33][34][35][36][37][38][39][40][41][42][43][44][45] thus generating from cheap commodity chemicals the required nucleophilic radicals which can subsequently add to the polarity-matched N-sulfonyl hydrazone.…”
Section: Main Textmentioning
confidence: 99%
“…The protocol was compatible with a broad set of acyclic/cyclic ethers and Ntriftosylhydrazones bearing a variety of substituents, delivering the desired homobenzylic ethers in good yield with high regioselectivity (Scheme 2A). 2 Note that a poor yield was obtained using N-tosylhydrazone (e.g., compound 6a, 96% and 35% yield, respectively). We were also successful at achieving intermolecular C(sp 3 )−H insertion with donor−donor carbenes for the first time, albeit in moderate yield (e.g., 6f and 6g).…”
Section: α-C(sp 3 )−H Bond Insertion Reaction Of Ethers With N-trifto...mentioning
confidence: 99%
“…1 In short, the coordination of ether to silver may affect the formation of silver carbine, but it does not modulate the reactivity of silver once it is formed. 2 3. DEFLUORINATIVE FUNCTIONALIZATION OF FLUOROALKYL N-TRIFTOSYLHYDRAZONES The synthesis and further functionalization of fluorinated compounds have attracted increased attention from chemists because these compounds are extensively used in organic synthesis and in the life and materials sciences.…”
Section: α-C(sp 3 )−H Bond Insertion Reaction Of Ethers With N-trifto...mentioning
confidence: 99%
“…38,39 Second, the weak carbene Ag = C bond with an electrophilic carbon would favor the formation of an ylide intermediate and the cleavage of this Ag − C bond to generate a free N-ylide. [40][41][42][43] Lastly, water could then act as a proton-transporter to facilitate the 1,2proton shift of N-ylide, thereby ensuring the selectivity of carbene N − H insertion. 44 This process represents an e cient and practical chemoselective carbene insertion into the N − H bonds of NH 3 •H 2 O, enabling the e cient synthesis of primary amines, including diaryl methylamines and α-amino acid esters, valuable building blocks for pharmaceuticals and agrochemicals.…”
Section: Introductionmentioning
confidence: 99%